PWE-244 The financial burden of narcotic bowel syndrome: a local experience. (22nd June 2015) - Johnson, MW; Prouse, T; Gibbons, M
Abstract : Introduction: Narcotic drugs are widely prescribed by both GPs and hospital physicians, but little consideration is afforded to the potential longterm issues when starting patients off on these addictive therapies. has escalated throughout UK. Between June–November 2014, 32, 956 prescriptions had been provided for strong opioid therapy in the Luton CCG catchment area. Not only is this a costly unchecked market, but much of this is taken for abdominal pain. Narcotic Bowel Syndrome (NBS) is under recognised and believed to be increasing in prevalence worldwide. NBS is a subset of opioid bowel dysfunction, characterised by chronic or frequently recurring abdominal pain that worsens with continued or escalating dosages of narcotics. We attempted to assess some of the financial cost implications of this condition on our local district general hospital in 2014. Method: In 2014 we started to collect the names of patients seen in gastroenterology clinics or during hospital admission where the clinician felt the patient was suffering from NBS. This was either thought to be the main cause or contributing factor to their symptomatology. During that year a retrospective analysis was performed reviewing the burden and cost of outpatient appointments and inpatient hospital admissions, using the hospital coding system and financial analysis. Results: A database collated the names of 41 patients with NBS. From the 1st of January to the 31st of December 2014, this cohort of patients made 78 hospital admissions (1.9 per patient) with an average length of stay (LOS) of 4.1 days. This was costed at £91, 310, or an average of £2, 227 per patient per year. In addition to that the same 41 patients made 159 outpatient appointments (3.9 per patient), costing £15, 639, or an average of £381 per patient per year. This small group of 41 patients cost a total of £106, 949 in 2014 or an average of £2, 608 per patient per year, in hospital inpatients admissions and outpatient appointments alone, before adding in their prescription costs. Conclusion: NBS is a poorly recognised condition that places a huge demand on the NHS system with regards to time, resources and finances. The prevalence of this condition is thought to be increasing. Early recognition could prevent a costly and potentially fatal pathway of deterioration. On average the annual financial cost of hospital base care for each NBS patients is £2, 608. Disclosure of interest: None Declared.